Acute versus staged surgical intervention in multiligamentous knee injuries: a review of the literature since 2009. Issue 5 (September 2015) - Barfield, William R.; Holmes, Robert E.; Slone, Harris; Walton, Zeke J.; Hartsock, Langdon A.
Abstract : Background: Our purpose was to determine whether recent literature provides evidence to favor either acute or staged surgical treatment of multiligamentous knee injury (MLKI). Because MLKI is uncommon and has a heterogeneous injury profile, conducting large trials has been challenging. Surgical intervention whether through repair or reconstruction is associated with high complication rates and significant morbidity. Currently, treatment recommendations are based on outcome studies composed mostly of level IV evidence. Methods: We searched the literature from 2009-2014. Eleven published studies met inclusion criteria. There were two level III studies and nine level IV studies. No level I studies met inclusion criteria. Results: Two-hundred seventy-four patients were identified; 201 males and 73 females. Thirty-nine percent (107) of the patients had a staged repair; 61% (167) of the patients had an acute repair. IKDC was the most consistently reported outcome measure, yet none of the studies reached statistical significance. Conclusions: Numerous studies have attempted to determine whether to repair or reconstruct the MLKI in an acute or a staged fashion. There is insufficient evidence to suggest superiority of outcomes for acute or staged treatment MLKI. Multicentered, prospective, randomized controlled trials are warranted to determine if there is any difference in outcomes between these two treatment strategies.